Realising a climate-resilient UK electricity and gas system - Metz,A; Darch,G; Workman,M (Proceedings of the Institution of Civil Engineers - Energy, 2016)
The risks presented by climate change mean that there is a need to future-proof the UK's energy (electricity and natural gas) infrastructure. The scale of investment required is estimated at more than £200 billion by 2030. Although there are a variety of funding sources available, increasing proportions of infrastructure investment are now being funded by the private sector. Therefore, it will be necessary to find ways to incentivise private investors to accommodate for adaptation requirements in their decision-making processes. Research was undertaken to explore the UK energy infrastructure under the following three main lenses. (a) What technical aspects of energy infrastructure need to consider the effects of climate change? (b) What investment is required in the near future to adapt to climate change? (c) What types of policy could create reliable signals for investment in climate change adaptation? This paper presents key findings and considerations for policy covering the three questions above: (a) there are data gaps, interdependencies not effectively assessed and techniques available but not yet adopted; (b) the investment community suffers from a lack of climate change expertise and a short-term mindset; and (c) there is a need for a clearer policy vision and greater collaboration.